Influence of site in the wood quality of Eucalyptus in plantations in Brazil. Issue 3 (3rd July 2019) - Barbosa, Thiago Leite; Oliveira, José Tarcísio da Silva; Rocha, Sofia Maria Gonçalves; Câmara, Ana Paula; Vidaurre, Graziela Baptista; Rosado, Antônio Marcos; Leite, Fernando Palha
Abstract : Genetic materials interact with the environment in specific ways, therefore their responses in wood need to be better understood. The present study sought to evaluate the influence of different climatic conditions in Minas Gerais, Brazil on Eucalyptus grandis × Eucalyptus urophylla wood . Two six-year-old clones were cultivated in Belo Oriente, Ferros, Santa Bárbara, Itabira and Peçanha. Five trees from each clone were sampled from the base to top direction. Wood density, heartwood/sapwood ratio, vessels, fibres, and extractive and lignin contents were determined, as well as their correlation with environmental variables. Vessel diameters, heartwood/sapwood ratio, and extractive and lignin contents all increased due to higher water availability in Santa Bárbara and Itabira. In both genetic materials, the variables linked to growth and wood quality were related to environmental factors.